HOUSEHOLD DECISION ANALYSIS ON ANIMAL PROTEIN FOOD CONSUMPTION: EVIDENCE FROM D.I YOGYAKARTA PROVINCE - Mujtahidah Anggriani Ummul Muzayyanah; Sudi Nurtini; Rini Widiati; Suci Paramitasari Syahlani; Tri Anggraeni Kusumastuti (Buletin Peternakan, 2017)
Food consumption pattern in Indonesia has change. Consumption of animal protein food is increasing as income increase. Animal protein foods are come from fish products and livestock products. The aim of this study is to analyze household decision on animal protein food consumption based on socioeconomics determinant of the households. Household expenditure data were used in this study. Discrete choice model is used to measure household decision in consuming these foods. Socioeconomics determinants are measured by Binary Logistic regression to know the influence of these to the household’s decision. Marginal effect value from binary logistic regression analysis showed that households tend to increase consuming animal protein food from livestock products varies from 0.5 to 6.09 times associated to socioeconomic factors of the households. Further research need to analyze nutritional status of the household’s members.